Simulasi dan Pelatihan Tanggap Bencana Gempa Bumi dan Kebakaran di SD Budi Utama Yogyakarta - Agustina Kiky Anggraini; Henda Febrian Egatama; William Wijaya (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
The community service was carried out at one of the educational institutions, Budi Utama Elementary School, which has around 500 students. Elementary school students need to understand basic rescue procedures when a disaster occurs. Community service was prioritized in the simulation and training of disaster responses, especially for earthquakes and fires. Earthquakes were one of the focus because this school was located in Yogyakarta, which was prone to this type of natural disaster. The fire was another focus because it usually occurs as a follow-up incident after the earthquake. The simulation and training on earthquakes and fires involved the Badan Penanggulangan Bencana Daerah (BPBD) DIY and UPT Damkar Sleman. The Budi Utama Elementary School community successfully carried out the rescue procedures based on the earthquake simulation. The training on firefighting showed success, too. The Budi Utama Elementary School community has successfully conducted disaster response simulations and training. The impact of these simulations and training was that the Budi Utama Elementary School community became aware of how to respond to a disaster.